Transports and water masses in the Fram Strait and its vicinity from three decades of hydrographic observations in 1980-2010 - Marnela, Marika (Helsingin yliopisto, 2016)
The Arctic Ocean and its exchanges with the Nordic Seas influence the north-European climate. The Fram Strait with its 2600 m sill depth is the only deep passage between the Arctic Ocean and the other oceans. Not just all the deep water exchanges between the Arctic Ocean and the rest of the world's oceans take place through the Fram Strait, but also a significant amount of cold, low-saline surface waters and sea ice exit the Arctic Ocean through the strait. Correspondingly, part of the warm and saline Atlantic water flowing northward enters the Arctic Ocean through the Fram Strait bringing heat into the Arctic Ocean. The oceanic exchanges through the Fram Strait as well as the water mass properties and the changes they undergo in the Fram Strait and its vicinity are studied from three decades of ship-based hydrographic observations collected from 1980-2010. The transports are estimated from geostrophic velocities. The main section, comprised of hydrographic stations, is located zonally at about 79 °N. For a few years of the observed period it is possible to combine the 79 °N section with a more northern section, or with a meridional section at the Greenwich meridian, to form quasi-closed boxes and to apply conservation constraints on them in order to estimate the transports through the Fram strait as well as the recirculation in the strait. In a similar way, zonal hydrographic sections in the Fram Strait and along 75 °N crossing the Greenland Sea are combined to study the exchanges between the Nordic Seas and the Fram Strait. The transport estimates are adjusted with drift estimates based on Argo floats in the Greenland Sea. The mean net volume transports through the Fram Strait are averaged from the various approaches and range from less than 1 Sv to about 3 Sv. The heat loss to the atmosphere from the quasi-closed boxes both north and south of the Fram Strait section is estimated at about 10 TW. The net freshwater transport through the Fram Strait is estimated at 60-70 mSv southward. The insufficiently known ...